The spirituality of hajj - Omer, Spahic (UNISSA Press, 2023)
The book deals with the spirituality and spiritual secrets of the major components of Hajj or the pilgrimage. The subjects of ihram, talbiyah, tawaf, sa’y, ‘Arafah, Muzdalifah, Mina and the city of Madinah as a holy city and the city of the Prophet, are covered. The subjects are organized in seven chapters which are interrelated and, as such, make up an edifying aggregate. As the final pillar of the edifice of Islam, Hajj denotes the attainment of one’s religious (spiritual) journey. It is its apex. It is likewise a manifestation, as well as affirmation, of one’s self-fulfilment. Hajj, in addition, is the proof of the efficacy of all the other pillars of Islam. Demonstrating how the physical realities of life are but an echo of, and the overture to, the metaphysical ones, Hajj is also an ultimate proof on its own. Analysing the above-mentioned subjects - and dimensions - of Hajj shows why and how such is the case. The objectives of the book are twofold: to contribute to the education of pilgrims and to help them penetrate, as well as experience, the deepest spiritual secrets of Hajj; and to contribute to the promotion and spread of the true message of Islam, in the process removing some of the many misconceptions about it. Hajj is a fabulous opportunity for Muslims to up the ante and work up the courage, for Hajj as a spiritual revolution in our world today is progressively attracting global attention. In its capacity as one of the largest concentrated and recurring religious festivals in the world, Hajj does not pass unnoticed. People are as much curious as they are fascinated and intrigued. Questions are asked and an increase both in the academic and pop(ular) demand is created. The ball is in Muslims’ court. In a certain sense, this book signifies a response, and is a humble step in the outlined direction. It follows especially the examples of Abu Hamid al-Ghazzali’s “The Book on the Secrets of Pilgrimage (Hajj)”, representing the Islamic classical culture, and Ali Shariati’s “Hajj: Reflections on Its Rituals”, representing contemporary times. The book invites other researchers to build on its content, and to thus contribute to the field of the roles of Hajj in remodelling the Muslim present-day consciousness and in reviving Islamic civilization. This is not a book written from a jurisprudential or fiqh perspective. Rather, the book is written from an interdisciplinary perspective that encompasses the scopes of more than a few Islamic scholarly disciplines. The term “spirituality” is the key, implying the inner dimensions of the Islamic worship in general and of the Hajj pilgrimage specifically. It also signifies the inherent devotional secrets that not only instigate but also take a pilgrim on and facilitate his spiritual journey of Hajj.